The Impact of Intramural Grants on Educators' Careers and on Medical Education Innovation. (June 2015) - Adler, Shelley R.; Chang, Anna; Loeser, Helen; Cooke, Molly; Wang, Jason; Teherani, Arianne
Abstract : Purpose: The University of California, San Francisco (UCSF), Haile T. Debas Academy of Medical Educators Innovations Funding program awards competitive grants to create novel curricula and faculty development programs, compare pedagogical approaches, and design learner assessment methods. The authors examined the principal investigators' (PIs') perceptions of the impact of these intramural grants on their careers and on medical education innovation. Method: At 12 months (project completion) and 24 months (follow-up), PIs submit a progress report describing the impact of their grant on their careers, work with collaborators, subsequent funding, project dissemination, and the UCSF curriculum. The authors analyzed these reports using qualitative thematic analysis and achieved consensus in coding and interpretation through discussion. Results: From 2001 to 2012, the program funded 77 PIs to lead 103 projects, awarding over $2.2 million. The authors analyzed reports from 88 grants (85.4%) awarded to 68 PIs (88.3%). PIs noted that the funding led to accelerated promotion, expanded networking opportunities, enhanced knowledge and skills, more scholarly publications and presentations, extramural funding, and local and national recognition. They also reported that the funding improved their status in their departments, enhanced their careers as medical educators, laid the foundation for subsequent projects, and engaged an array of stakeholders, including trainees and junior faculty. Conclusions: These modest intramural education grants not only created innovative, enduring programs but also promoted educators' professional identity formation, fostered collaborations, supported junior faculty in finding their desired career paths, provided advancement opportunities, and raised the local and national profiles of recipients.